Genotoxic impurities in medicinal products – regulatory requirements - Čarapić, Marija; Nikolić, Katarina; Agbaba, Danica (Archives of Pharmacy, 2022)
Most chemical syntheses use highly reactive molecules, which are often DNA-reactive (mutagens). They may be present in the active substance (AS) or in the drug product as genotoxic impurities (GI). The mechanism of action of most GIs is based on DNA modification by direct binding (electrophilic - alkylating agents), insertion into the DNA chain (topoisomerase inhibitors) and antimetabolites (purine/pyrimidine analogs). Structural alerts (SA) for carcinogenic activity are defined as functional groups or substructures of compounds associated with carcinogenic activity. SA indicates a chemical group that causes toxic effects through one or several common mechanisms of action. GIs can bind directly to DNA or after metabolic transformations (oxidation and reduction), thus the SA structure may indicate the formation of several toxic metabolites. The risk assessment for the presence of GIs is a mandatory part in the module 3 (AS/DP impurity profile) submitted in the marketing authorization procedure, also in the approval of clinical trials. Guideline ICHM7 provides recommendations for identification, categorization, qualification and control strategy of mutagenic impurities in order to limit the potential carcinogenic risk. According to ICHM7, the classification (class 1-5) of all impurities is performed on the basis of data on carcinogenicity and bacterial mutagenicity (BM) from databases/scientific literature. If data are not available, computational toxicological assessment (QSAR) is performed and BM is predicted with two independent models. If any of model shows SA structures, a BM assay (Ames test) is performed. The high potent mutagenic carcinogens (aflatoxins, nitrosamines, alkyl-azoxy compounds) referred to as “cohort of concern”.